Dependencia con la presión del índice de refracción del AgGaS_2 - Power, Ch.; Calderón, E.; González, J.; Chervin, J.C. (Revista Mexicana de Física, 2011)
In this work, we study the pressure behavior of the optical absorption spectrum of a single crystal AgGaS_2, taking measurements in the infrared energy range from 0.30 up to 0.70 eV for pressures values P below 4GPa and room temperature T, using a diamond anvil cell in combination with infrared micro spectroscopy technique [1]. With this study, we determine the refraction index n variations in terms of pressure within the stability range of the chalcopyrite structure [2-6] as well as the changes under pressure of both the static (ε _0) and high frequency (ε _∞ ) dielectric constants. These results can be compared with the experimental values reported by Boyd et al. [7].